Critical Raw Materials Deposits Map of Mainland Portugal: New Mineral Intelligence in Cartographic Form. (3rd July 2021) - de Oliveira, Daniel P. S.; Filipe, Augusto; Gonçalves, Pedro; Santos, Sara; Albardeiro, Luís
ABSTRACT: Reliable and unhindered access to raw materials is a growing concern within the EU and across the globe and the demand for Critical Raw Materials (CRM) plays a crucial economic role in most developed countries around the world. These are of extreme importance for supply chains regarding new technologies, sustainability issues and carbon footprint reduction. The definition of a continuously updated list of CRM by the European Commission led to the first CRM Map of Europe in 2016. Following this, several countries have been surveying, preparing, and evaluating their mineral occurrences to create a resources/deposits database and, therefore, to create a CRM map of their own. With this purpose in mind, we present and explain the first Critical Raw Materials Deposits Map of mainland Portugal, at 1:700, 000 scale. This paper describes the scientific, technical, and graphical methodologies involved in its design.